BIOPOLITIK DAN KRISIS KEDAULATAN DALAM NOVEL LAMPUKI KARYA ARAFAT NUR: BIOPOLITICS AND THE CRISIS OF SOVEREIGNTY IN ARAFAT NUR’S LAMPUKI - Dewojati, Cahyaningrum; Arifin, Moch. Zainul (Jurnal Pengajian Melayu (JOMAS), 2021)
Abstract This research aims to analyse the biopolitics and sovereignty crisis in Arafat Nur’s novel, Lampuki (2011). The method used in this research was the literary method with data collection, which was by utilising the listening and dialectical methods. This research used Giorgio Agamben’s biopolitical theory. The results indicate that the biopolitical transformation of the Achehnese society to the Indonesian state moved into the inclusion process from zoe to bios. However, there are research gaps in the area of inclusion, namely bare life. The Achehnese were not automatically brought into a new political order, but they were circling the area between inclusion and exclusion as well as the politicisation of life. In addition to the past history, the sovereignty crisis occurred and was officially declared by the government. As a consequence from the state of exception, the homo sacers in the novel, Lampuki tend to be civilians. The novel does not merely re-present past conflicts, but also implicitly shows root causes of conflict from biopolitics. Keywords: Biopolitics, State of Exception, Homo Sacer, Novel Lampuki.